LEVEL OF INTEREST IN MARKETING MIX FACTOR LATEX GLUE BUYING DECISION - Duangnil, Preyawat; Worapishet, Thirarut (Journal of MCU Nakhondhat, 2022)
The objectives of this research article were 1) to study the criteria according to the marketing mix factors that consumers employ before buying latex glue, 2) to study individual factors of consumers, 3) to study the purchaser’s behavior for buying latex glue, 4) to study the difference of criteria according to the marketing mix factor that consumers use to buy latex glue classified by personal factors, 5) to study the difference of criteria according to the marketing mix factors that consumers use to buy latex glue classified by consumer purchasing behavior. In this independent study, the population studied were general people who have bought or used latex glue retail use. The sample used in this study was 482 general people buying or using latex glue purchase. A simple random sampling method was mainly used. The questionnaire was utilized as a tool to collect data. The statistics employed for data analysis were percentage, mean, standard deviation, t-test, and F-test (One Way ANOVA). The statistical significance level was 0.05. The research found that the consumer’s gender and the number of children in the family which were different influenced the decision to the marketing mix factors to purchase the latex glue products differently; different average monthly income considered by the marketing mix factors for the decision to purchase latex glue products is indifferent. In terms of buying behavior, it was found that consumers purchasing volume and having a different purpose for the purchase, paying attention to different marketing mix factors affected the purchasing decision of latex glue. Influencers in purchasing decisions and different purchasing channels pay attention to the marketing mix factors in the decision to purchase latex glue is indifferent.